Anesthesia Management of a Child with Mosaic Trisomy 22 for Adenotonsillectomy Surgery - Masoud Tarbiat; Mohammad Hossein Bakhshaei; Rohollah Abbasi; Mahmoud Rezaei (Archives of Anesthesia and Critical Care)
Mosaic trisomy 22 is a very rare autosomal anomaly with variability of organ malformations and developmental defects. There are fewer than 23 reports in the literature of live born children describing their neurodevelopmental outcome. Sometimes in clinical practice, anesthesiologists confront a rare clinical case with no paper published on it or having previous experience about it. Therefore, they face a serious challenge in anesthesia managing and selecting drugs for them (like our case). So, we reported our experience about a child (aged 8) with mosaic trisomy 22 who had anesthesia for adenotonsillectomy surgery.  Previously, he had a history of seizure and variety of surgeries for congenital anomalies. He also had been treated for congenital hypothyroidism and gastroesophageal reflux disease. The anesthesia performed with midazolam, fentanyl, sodium thiopental, atracurium and isoflurane in O2:N2o (50:50). The operation was uneventful and he was completely awakened in recovery room. This report emphasizes that in some situation, this approach could be used safely for anesthesia management in these patients.